Dynamic property of chloride-selective electrode and its application to sea-water concentrates - OGATA, Noboru (BUNSEKI KAGAKU, 1972)
A dynamic property of the chloride-selective electrode has been studied for the determination of chloride in sea-water concentrates by means of a direct potentiometric measurement. A solid-state electrode for chloride (Orion, model 94-17) and a double-junction type reference electrode (Orion, model 92-02) were used. The outer bridge solution in the reference electrode used was 10% solution of potassium nitrate. When the components in the solution is quite different, an accurate determination was difficult because the electrode potential was affected by the junction potential, the activity coefficient of chloride and the presence of bromide. The junction potential was decreased by the use of saturated solution of potassium nitrate as bridge solution, but the removal of these effects was not so enough as to make a quantitative determination. The effects of the junction potential and the activity coefficient were removed by dilution of the sample with 10% solution of potassium nitrate which is the same solution as the bridge solution, but the effect of bromide still remained. The response time slowed down when the concentration of chloride was high, when the concentration was reduced from high to low and when bromide was present. In these case, the restoration of electrode to the normal state required a long time. The variation of temperature caused an effect approximately twice of the calculated value by the Nernst's equation. Chloride in sea-water concentrates could approximately be determined from the calibration curve obtained by using sodium chloride solution. On the other hand, the chloride content in sample solutions in which the composition varies only slightly, eg. seawater, brine and bittern of the same manufacture, and solutions of common salt, could be determined rather exactly from the calibration curve made by using the sample solution. The standard deviation in these measurements was 0.016 M in sea-water (the range of 0.32 to 0.74 M), 0.023 M in brine (the range of 2.4 to 3.7 M), 0.016 M in bittern (the range of 5.1 to 5.6 M), and 0.62% in the solution of common salt(the range of 90 to 100% as sodium chloride). Thus the determination became feasible for a wide range of constituent, except when the bromide content varied remarkably, by a dilution of the sample with the bridge solution. In this case, the potential in sea-water and in brine was 3 mV lower than in simple solutions of sodium chloride and the standard deviation was 0.0015 M in the range of 0.02 to 0.06 M after the dilution.